2014
DOI: 10.1016/j.cell.2014.04.053
|View full text |Cite
|
Sign up to set email alerts
|

A DNA-Dependent Protease Involved in DNA-Protein Crosslink Repair

Abstract: Toxic DNA-protein crosslinks (DPCs) arise by ionizing irradiation and UV light, are particularly caused by endogenously produced reactive compounds such as formaldehyde, and also occur during compromised topoisomerase action. Although nucleotide excision repair and homologous recombination contribute to cell survival upon DPCs, hardly anything is known about mechanisms that target the protein component of DPCs directly. Here, we identify the metalloprotease Wss1 as being crucial for cell survival upon exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
391
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(440 citation statements)
references
References 64 publications
33
391
0
3
Order By: Relevance
“…13 It has been suggested that in vivo either ubiquitin-mediated proteolysis or the action of the Wss1 protease acts on the Top1-cc to create an intermediate that is amenable to further processing by Tdp1. 16 This hypothesis is supported by the synthetic lethal genetic interaction between wss1 and tdp1. 17 Our studies have revealed an unexpected role for the Sgs1 helicase in mutation avoidance stemming from the Top1-mediated cleavage at rNMPs in DNA.…”
Section: Discussionsupporting
confidence: 49%
“…13 It has been suggested that in vivo either ubiquitin-mediated proteolysis or the action of the Wss1 protease acts on the Top1-cc to create an intermediate that is amenable to further processing by Tdp1. 16 This hypothesis is supported by the synthetic lethal genetic interaction between wss1 and tdp1. 17 Our studies have revealed an unexpected role for the Sgs1 helicase in mutation avoidance stemming from the Top1-mediated cleavage at rNMPs in DNA.…”
Section: Discussionsupporting
confidence: 49%
“…The methods lack specificity for the chemical composition of DPCs (Stingele et al, 2014;Zhitkovich and Costa, 1992;Shaham et al, 1996Shaham et al, , 2003. Moreover, they cannot differentiate between exogenous and endogenous formaldehyde-induced DPCs.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent bioinformatic search defined a minimal VIM consensus sequence and identified several additional VIM-containing proteins [63]. These include ANKZF1 (ANKyrin repeat and Zinc Finger domain-containing-1, also known as ZNF744 or Vms1), a protein that has been implicated in mitochondrial protein degradation [64]; the UBX protein UBXD1, involved in sorting of ubiquitylated cargo in the endocytic pathway [10]; AIRAPL (Arsenite Inducible RNA Associated Protein Like Protein, also known as ZFAND2B), an ER membrane-anchored protein which associates with and regulates the function of the 26S proteasome under arsenite stress [65]; SelS (also called VIMP, VCP-Interacting Membrane Protein), a protein involved in the recruitment of p97 to the ER membrane [66]; and the yeast protein Wss1, a metalloprotease involved in DNA-protein crosslink repair [67]. With the exception of SelS it was shown that these proteins interact via their VIM with p97 [63,64,[67][68][69].…”
Section: The Vcp-interacting Motifmentioning
confidence: 99%
“…In mammals, the motif is found in the SEP (Shp, eyesclosed, p47) domain-containing UBX proteins p47, p37, UBXD4 and UBXD5, where it is located N-terminally of the UBX domain [46], to which it is connected via a mainly unstructured linker. Further mammalian members are the UBX protein TUG (also known as ASPL) [77], UFD1 [50], DVC1 (also called Spartan, a homolog of yeast Wss1), a proteolytic enzyme that functions in DNA repair coupled to DNA replication [67,78], and the Derlin proteins DER1 and DER2 involved in endoplasmic reticulum associated protein degradation (ERAD) [66,[79][80][81]. Currently, only limited structural information on the SHP box-p97 interaction is available, and the exact binding site of the SHP box on the p97 N domain remains unclear.…”
Section: Shp Box/bs1mentioning
confidence: 99%